Omalizumab Reduces Unplanned Healthcare Interactions in Irish Patients With Chronic Spontaneous Urticaria - Ridge, Katie; Redenbaugh, Vyanka; Conlon, Niall (Frontiers in Allergy, 2021)
Chronic spontaneous urticaria (CSU) is a common, debilitating skin disorder associated with impaired quality of life and psychological comorbidity. Symptoms can be difficult to control and many individuals will not respond to first line treatment. Due to the chronic and unpredictable nature of the disorder, patients frequently have repeated healthcare attendances. Despite this, little is known about healthcare resource utilization internationally. Furthermore, there is no Irish data to inform fundholding decision makers. Omalizumab is an anti IgE monoclonal antibody used in refractory urticaria. It is a comparatively high cost medicine and access to this treatment can be challenging. Recent assessments of omalizumab compared with usual care suggest that omalizumab is a cost-effective treatment for refractory urticaria. We carried out a retrospective review of 47 patients commenced on omalizumab. We evaluated unplanned primary and secondary care attendances and urticaria symptomatology before and after treatment. As expected, patients with refractory symptoms that were commenced on omalizumab had objective improvements in urticaria symptoms. Importantly, we show that this is reflected in a dramatic reduction in unplanned healthcare interactions at primary care and emergency departments. These data suggest that omalizumab may benefit these patients by reducing disease activity and thereby reducing the need for unplanned healthcare interactions.